INTESTINAL OBSTRUCTION DUE TO STRONGYLOIDES STERCOLARIS: ABOUT A CASE.: OBSTRUCCIÓN INTESTINAL POR STRONGYLOIDES STERCOLARIS: A PROPÓSITO DE UN CASO - Tapia Barcellandi, Rolando (2024)
ABSTRACT Strongyloidiasis commonly causes gastrointestinal problems. We present the case of a male, a 30-year-old cadet in the Peruvian Navy from Lima, who developed a hyperinfection syndrome due to Strongyloides stercoralis, having a presumptive diagnosis of polymyositis for which he received a short cycle of corticosteroids. He was not a carrier of the HTLV 1/2 virus. Upon admission, he presented with hyporexia, generalized weakness, cachexia, intermittent self-limited diarrhea, oral intolerance, and mild abdominal distension. The patient reached the dissemination stage, resulting in severe intestinal damage. The low excretion of larvae in the feces made the diagnosis difficult. Treatment was provided with parenteral ivermectin at a dose of 1.2ml subcutaneously every 48 hours for three doses, with a good clinical response and subsequently good oral tolerance. The importance of presenting the case is to comment on the diagnostic and therapeutic approach to this endemic geohelminthiasis of Peru.